From benchmarking to best practices: Lessons from the laboratory quality improvement programme at the military teaching hospital in Cotonou, Benin - Zohoun, Alban (Afr J Lab Med, 2021)
BACKGROUND: In 2015, the Army Teaching Hospital–University Teaching Hospital (HIA-CHU [Hôpital D’instruction des Armées de Cotonou Centre Hospitalier et Universitaire]) laboratory in Benin launched a quality improvement programme in alignment with the World Health Organization Regional Office for Africa’s Stepwise Laboratory Improvement Process Towards Accreditation (SLIPTA). Among the sub-Saharan African laboratories that have used SLIPTA, few have been francophone countries, and fewer have belonged to a military health system. The purpose of this article was to outline the strategy, implementation, outcomes and military-specific challenges of the HIA-CHU laboratory quality improvement programme from 2015 to 2018. INTERVENTION: The strategy for the quality improvement programme included: external baseline SLIPTA evaluation, creation of work plan based on SLIPTA results, execution of improvement projects guided by work plan, assurance of accountability via regular meetings, training of personnel to improve personnel competencies, development of external stakeholder relationships for sustainability and external follow-up post-SLIPTA evaluation. LESSONS LEARNT: Over a period of 3 years, the HIA-CHU laboratory improved its SLIPTA score by 29% through a quality improvement process guided by work plan implementation, quality management system documentation, introduction of new proficiency testing and internal quality control programmes, and enhancement of personnel competencies in technical and quality management through training. RECOMMENDATIONS: The programme has yielded achievements, but consistent improvement efforts are necessary to address programme challenges and ensure continual increases in SLIPTA scores. Despite successes, military-specific challenges such as the high mobility of personnel have hindered programme progress. The authors recommend that further implementation research data be shared from programmes using SLIPTA in under-represented settings such as military health systems.